FACTORS OF PSYCHOLOGICAL PREPAREDNESS TO FINANCIAL INDEPENDENCE IN THE STUDENTS - Drobysheva, T.V. (Modern Psychology, 2019)
The paper describes the indicators of psychological readiness of students for financial independence: the ability to plan expenses, the ability independently solve their financial problems, to choose the optimal strategies of economic behavior to maintain financial stability. All of them connected with the preparedness of young people to gain financial independence, regardless of any circumstances. The life position of the respondents was a system-forming factor of psychological readiness for financial independence. It’s based on the importance of value orientations associated with the professional self-realization of students, their internal locus of control.